Butylphthalide Inhibits Autophagy and Promotes Multiterritory Perforator Flap Survival - Li, Baolong; Chen, Zhengtai; Luo, Xiaobin; Zhang, Chenxi; Chen, Hongyu; Wang, Shuxuan; Zhao, Mengyao; Ma, Haiwei; Liu, Junling; Cheng, Mengshi; Yang, Yanyan; Yan, Hede (Frontiers in Pharmacology, 2021)
Multiterritory perforator flap is an important plastic surgery technique, yet its efficacy can be limited by partial necrosis at the chokeⅡzone. Butylphthalide (NBP) has been used in many diseases, but has not been studied in the multiterritory perforator flap. With the effect of NBP, we observed increasing in capillary density, inhibition of autophagy and oxidative stress, and a reduction in apoptosis of cells, all consistent with increased flap survival. However, the protective effect of NBP on multiterritory perforator flap was lost following administration of the autophagy agonist rapamycin (Rap). Through the above results, we assumed that NBP promotes flap survival by inhibiting autophagy. Thus, this study has found a new pharmacological effect of NBP on multiterritory perforator by inhibiting autophagy to prevent distal postoperative necrosis through exert effects on angiogenesis, oxidative stress, and apoptosis within the flap.